Improved Known‐Key Distinguisher on Round‐Reduced 3D Block Cipher. Issue 1 (1st January 2015) - Zha, Daren; Wu, Shuang; Wang, Qiongxiao
Abstract : The 3D block cipher is a three‐dimensional version of AES(Advanced encryption standard), which use a three‐dimensional state and similar round functions. In this paper, we will use the known‐key attack model proposed by Knudsen and Rijmen, and propose an improved distinguisher on 15 rounds of 3D, which has 22 rounds in total. The distinguisher is constructed using rebound techniques. In the previous distinguisher, only three inbound phases are merged. Here we propose a method to merge four inbound phases using gradual matching techniques. The improved complexity of this distinguisher is 2128 computations and 264 memory. The computational complexity is significantly reduced from 2200 in the previous attack.